The Effect of the Combination of Black Soybean Tempeh Extract (Glycine max (L.) Merril) and Purple Sweet Potatoes (morning glory potatoesL.) on Leptin Hormone Levels in DMT2 Model Rats - Anggraini, Atika; Rahmawati, Jevi Milda; Lestari, Sri Rahayu; Gofur, Abdul (Al-Hayat: Journal of Biology and Applied Biology, 2023)
Diabetes mellitus (DM) is a metabolic disorder characterized by chronic hyperglycemia. The prevalence of DM has been reported to increase from year to year. T2DM is characterized by insulin resistance, Leptin have an effect on insulin secretion, glucose and insulin will decrease due to leptin secretion. However, low levels of leptin that exceed the normal limit will interfere with insulin work so that it triggers diabetes caused by insulin resistance. Black soybean tempeh and purple sweet potato have therapeutic potential for people with T2DM. Both contain high antioxidants This study aims to determine the effect of the combination of black soybean tempeh extract and purple sweet potato on leptin hormone levels in DMT2 rat model. The experimental animals in this study were male white rats of the wistar strain which were divided into 6 groups. Preparation of hyperglycemic rats by feeding high-fat diet for 30 days, 10% sucrose drink for 30 days and streptozotocin injection at a dose of 35 mg/kg BW in 0.1 citrate buffered saline pH 4.5. Treatment using extract and purple sweet potato for 30 days. Mice were dissected and blood serum was taken for analysis of leptin hormone levels. Based on the results of the research data, there was an effect of the combination of black soybean tempeh extract and purple sweet potato on the leptin hormone levels in DMT2 rat model.